2015
DOI: 10.3109/10428194.2014.990010
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy with rituximab may be better than radiotherapy alone in first-line treatment of early-stage follicular lymphoma: is it time to change the standard strategy?

Abstract: Early-stage follicular lymphoma (FL) has traditionally been treated with involved-field radiotherapy (RT). Rituximab (R) is a low-toxic, efficient systemic therapy for FL, but there are no data about its clinical impact in early FL. We retrospectively analyzed 93 patients with stage I-II indolent FL treated with RT (n=65) or RT+R (n=14) or R alone (n=14). Median follow-up was 5.0 years for patients with RT, 2.8 years for the RT+R subgroup and 2.5 years for patients treated with R. The complete response rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Although the use of chemotherapy decreased from 43% to 36%, use of single‐agent chemotherapy doubled from 5.4% in 1999 to 11.7% in 2006 (Fig. ), which may be related to the promising results noted with single‐agent rituximab . In the late 1990s to early 2000s, several studies demonstrated the benefits of rituximab, predominantly in patients with advanced or recurrent/refractory follicular lymphoma .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of chemotherapy decreased from 43% to 36%, use of single‐agent chemotherapy doubled from 5.4% in 1999 to 11.7% in 2006 (Fig. ), which may be related to the promising results noted with single‐agent rituximab . In the late 1990s to early 2000s, several studies demonstrated the benefits of rituximab, predominantly in patients with advanced or recurrent/refractory follicular lymphoma .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have reported that PFS or disease-specific survival improved more after systemic chemotherapy than after irradiation alone or with a WW strategy. 11,31 However, other studies have not found such improvements; 21,24 therefore, the importance of systemic therapy remains debatable. Recently, R has become the preferred candidate for systemic therapy in terms of adverse events such as SPM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, R has become the preferred candidate for systemic therapy in terms of adverse events such as SPM. A recent observational study demonstrated excellent survival for patients treated with R with or without irradiation, 11,32,33 although the follow-up period was not long enough to estimate clinical outcome. As most of these studies were retrospective in nature, prospective trials are needed to clarify future directions of treatment for early-stage FL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dogma of early-stage, indolent lymphoma as a pure localized disease (amenable to cure with RT) has to be challenged, as nearly half of patients with early-stage FL will relapse within ten years, almost exclusively in distant non-irradiated areas [17]. It should be noted that with the increasing integration of PET-CT into initial management, improved staging accuracy may translate into improved disease control and survival rates for early-stage FL, by excluding patients with occult, distant disease [18].…”
Section: Introductionmentioning
confidence: 99%